Study and Realization of a Photovoltaic System With an MPPT Control - عبد الكريم, ضو (University of El-Oued, 2022)
"Photovoltaic (PV) energy is increasingly gaining its place in alternative energy sources, but solar panels, despite the development in manufacturing techniques, suffer from a rather low energy conversion efficiency, and this efficiency can be lower if the photovoltaic generator (PVG) is not working. Around a point called: the maximum power point MPP. The pursuit of this point, which changes location with climatic conditions, is a very important step in the operation of the PV system. In this thesis, we will simulate, improve and realize a DC- DC step-down and step-up photovoltaic system. This study covers the implementation of various max power point algorithms such as perturbation and control (O&P) algorithm, additional conduction (InC), Cuckoo search (CS) that we will start by simulating and modeling the photovoltaic and DC-DC step-down transformer according to the mathematical model, after that, we detail several MPPT algorithms that control our converter. Finally, we have achieved the practical application of our system with the three proposed MPPT algorithms based on the 2560 Arduino Mega board." "تكتسب الطاقة الكهروضوئية(PV) ماكانتها بشكل متزايد في مصادر الطاقة البديلة، لكن الالواح الشمسية، على الرغم من التطور في تقنيات التصنيع، تعاني من كفاءة تحويل طاقة منخفضة إلى حد ما، ويمكن أن تكون هذه الكفاءة أقل اذا لم يعمل المولد الكهروضوئي (PVG) حول نقطة تسمى: نقطة الطاقة القصوى MPP .يعد السعي وراء هذه النقطة، التي تغير الموقع مع الظروف المناخية، خطوة مهمة للغاية في تشغيل نظام الكهروضوئية. سنقوم في هذه الأطروحة بمحاكاة وتحسين وتحقيق نظام كهروضوئي يعمل مبحول DC-DCالخافض والرافع لجهد. تغطي هذه الدراسة تنفيذ خوارزميات مختلفة لأقصى نقطة للطاقة مثل خوارزمية الاضطراب والمراقبة (O&P)، والتوصيل الاضافي (InC)، Cuckoo search (CS) ذلك سنبدأ بمحاكاة ونمذجة الخلية الضوئية ومحول DC-DCالخافض والرافع لجهد وفقًا للمنوذج الرياضي، بعد ذلك، قمنا بتفصيل العديد من خوارزميات MPPT التي تتحكم في المحول الخاص بنا. أخير، حققنا التطبيق العملي لنظامنا مع الخوارزميات الثلاثة المققترحة MPPT استنادا الى لوحة 2560 Arduino Mega ."
مذكرة ماسترتخصص تحكم كهربائي
Keywords: P&O ،INC ،CS ، 2560 Arduino Mega ،MPPT.; مولد الطاقة الكهروضوئية، ، P&O ،INC ،CS ، 2560 Arduino Mega ،MPPT.